Slow release potash fertilizer - Agudo, Rowena Victoria B. (College of Engineering, 1995)
Product: Slow release potash fertilizer -- Plant location: Munoz, Nueva Ecija -- Annual volume of production: 8,184,000 kg -- Annual gross sales: P 67,518,000 -- Annual income: P 17,093,920 -- Total capital investment: P 66,573,738 -- Product unit cost: P 2.78/kg -- Suggested product selling price: P 8.25/kg -- Return on investment: 65.22% -- Breakeven capacity: 1,145,760 kg/year -- Payback period: 1.75 years